O uso da marcação de gênero neutro no Twitter por uma perspectiva sociolinguística - Baldez, Diovana da Silveira (2022)
The main purpose of this research is to investigate the use of gender-neutral marking in Portuguese: a still recent linguistic variation phenomenon, which divides many opinions in social and political circles. The choice of the theme is justified given the interest, as linguists, to analyze language as an organism in constant construction and resignification, capable of materializing different worldviews, through which different identities are established. Thus, the Theory of Variation (LABOV, 2008 [1972]; WEINREICH; LABOV; HERZOG, 2006 [1968]), with a focus on Communities of Practice (ECKERT; MCCONNELL-GINET, 1992a, 1992b) support the description and analysis conducted. As a means of observing the variant, the social network Twitter was considered, in which we collected 3,446 tweets produced by three subjects during the second half of 2020, who explicitly express a preference for the use of the neutral pronouns “Elu”, “Ilu”, “El” or “Ile”. As a selection criterion, tweets containing adjectives, nouns and pronouns whose referent was characterized by a human were considered, in which the gender distinction occurred morphologically by gender marks. The predictor variables stipulated were Morphosyntactic Class, Syntactic Function, Lexical Item, the tweet Topic, Gender Agreement, the reference performed by gender marks (generic or specific) and the month in which the tweet was written. The collected sample was submitted, through the RStudio interface, to version 4.1.2 of the R program, through which the proposed statistical treatment was carried out. The results obtained pointed as conditioners of gender-neutral employment the Adjective class, the topics of Affective Relationship and Identity and the Generic Reference performed by gender marking, as well as the syntactic function of Predicative and the Generic Reference in relation to Participants A and C specifically, which have a lower percentage of gender-neutral use. Indicating a disadvantage regarding gender-neutral marking, the Agree with Referent factor was observed, related to Gender Agreement variable, in the data sample of Participants A and B.